Improving the Quality of Healthy Aging Care: Participatory Action Research - Hamidreza Zendehtalab; Zohreh Vanaki; Robabeh Memarian (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives: In elderly care provided by health centers, healthy elderly are neglected in care and education. This qualitative study aimed to standardize healthy ageing care. Methods & Materials: This community-based participatory research with 4 steps (problem detection-design of change programs-implementation of interventions-evaluation) was conducted from 1395 to 1397 in Motahari Health Center of Mashhad, with the participation of 11 health care provider, 54 healthy elderly and 54 family members. The Mean±‌SD age of caregivers was 32.4‌±2.7 years and their mean work experience was 8.3 years. The Mean±‌SD age of the elderly was 64.3‌±‌3.9 years. Data were collected through SERVQUAL questionnaire, interviews, focus group discussions, and field notes. After identifying problems through interviewing 8 staff and 19 seniors, Group discussion sessions were held to design the program. After implementing the change plans, 30 interviews with the participants were conducted again and the comparisons were done and evaluated before and after the change plans. For qualitative content analysis, the method of describing reality was used, and for analyzing quantitative data, descriptive statistics and paired t-test were used. Results: Designed program care could be improve healthy aging care in the health center environment by modifying attitudes, skills and staff empowerment. The Mean±‌SD of quality of care for the elderly and their families in the pre-intervention phase was 63.02‌±‌9.46 and 61.83‌‌‌±‌9.05, respectively. In the post-intervention phase, these values reached 130.19‌±‌14.75 and 122.65‌±‌13.56, respectively, which were statistically significant (P=0.001). Conclusion: The community-based participatory research promoted the quality of elderly services with features such as active, participatory, continuous, comprehensive and supportive care. So this model can be used in other health centers.